Assessing Mentoring Culture: Faculty and Staff Perceptions, Gaps, and Strengths - Sheridan, Lynn Marie Marthe; Hubbard Murdock, Natasha; Harder, Emily (Canadian Journal of Higher Education, 2015)
The purpose of this non-experimental, cross-sectional, descriptive research was to survey faculty and staff perceptions of mentorship in a postsecondary institution in order to determine gaps and strengths in the current mentorship environment. The anecdotal activities we present reflect our educational practice environment through the work of our Mentorship Team. Data were collected utilizing Zachary’s Mentor Culture Audit tool. The culture building block measured 4.65 on a 7-point Likert scale, suggesting the presence of a weak mentorship culture. However, the infrastructure building block measured only 3.41, showing that organizational resources and supports are below average. We also present eight hallmark category results to further identify strengths and gaps. This is the first assessment of our mentoring culture at an organizational level. Other postsecondary institutions may benefit from formally assessing the gaps in and strengths of their mentorship culture to assist them with acquiring adequate resources to further develop and sustain their mentoring activities.